Structural characteristics of locust bean gum hydrolysate and its alleviating effect on dextran sulfate sodium-induced colitis - Jiang, Kangjia; Wang, Duo; Su, Le; Liu, Xinli; Yue, Qiulin; Li, Baojun; Li, Kunlun; Zhang, Song; Zhao, Lin (Frontiers in Microbiology, 2022)
(1) Background: Ulcerative colitis (UC) is an inflammatory lesion of the colon from various causes. As current therapeutic drugs have adverse effects on patients with UC, there is a growing demand for alternative medicines from natural and functional foods. Locust bean gum, as a dietary fiber, has a variety of physiological effects. (2) Methods: In the present study, locust bean gum hydrolysate (LBGH) was obtained from the acid hydrolysis of locust bean gum. The structure of LBGH was characterized by thin-layer chromatography and HPLC-ESI-MS/MS analysis. And we investigated the therapeutic effect of LBGH on a mouse model of dextran sulfate sodium (DSS)-induced colitis. (3) Results: It was observed that the LBGH consisted of a mixture of monosaccharides and oligosaccharides with a degree of polymerization (DP) 2-7. LBGH treatment dramatically alleviated colonic pathological damage, suppressed the overproduction of pro-inflammatory factors and the activation of nuclear factor κB (NF-κB), increased the mRNA expression of tight junction proteins, and increased the abundance of probiotics such as Lactobacillus and Bifidobacterium in the gut. (4) Conclusion: There is a correlation between these mitigating effects on inflammation and the treatment of LBGH. Therefore, LBGH has tremendous potential in the treatment of colitis.